2008
DOI: 10.1002/dei.247
|View full text |Cite
|
Sign up to set email alerts
|

Information about support services for families of young children with hearing loss: A review of some useful outcomes and challenges

Abstract: This paper is concerned with reviewing some useful effects of information about support services provided to families of young children with hearing loss and the challenges of providing this information to families. Evidence indicates that 95 per cent of young children with hearing loss have hearing parents. With no previous experience of hearing loss, these families are faced with numerous challenges in raising these children. They require timely and unbiased information that could enable them to respond appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…These findings were also supported in the Roberts et al (2015) study where some parents reported “feeling pushed by professionals who appeared to have their own biased agenda” (p.947). Given the significant role professional influence plays in this process, it is therefore imperative that audiologists, and other health professionals, provide parents with comprehensive and accuate information regarding all habilitation options (Bekker et al, 1999; Marteau et al, 2001), without any undue bias (Eleweke et al, 2008) thereby allowing parents to make an informed decision regarding their child’s early intervention (Moeller et al, 2013). When making an informed decision, parents must consider two important principles: (1) the decision should be a reflection of the individual’s values; and (2) the decision should be based on relevant and quality information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings were also supported in the Roberts et al (2015) study where some parents reported “feeling pushed by professionals who appeared to have their own biased agenda” (p.947). Given the significant role professional influence plays in this process, it is therefore imperative that audiologists, and other health professionals, provide parents with comprehensive and accuate information regarding all habilitation options (Bekker et al, 1999; Marteau et al, 2001), without any undue bias (Eleweke et al, 2008) thereby allowing parents to make an informed decision regarding their child’s early intervention (Moeller et al, 2013). When making an informed decision, parents must consider two important principles: (1) the decision should be a reflection of the individual’s values; and (2) the decision should be based on relevant and quality information.…”
Section: Discussionmentioning
confidence: 99%
“…As well as the need for adequate and accurate information, parents also need to be provided with appropriate emotional support during the potentially difficult time of diagnosis (Eleweke et al, 2008). Participants in both phases of the present study reported feeling overwhelmed at the time of diagnosis, with a range of emotions expressed that are typical of the feelings experienced by parents as they move through a cycle of grief (Kampfe, 1989; Kurtzer-White & Luterman, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents may need professional support as they shape their expectations for their child's progress as well as for the expectations of other family members regarding life with a deaf family member (Spahn, Richter, Burger, Lohle, Wirsching, 2003). These are needs for support that many hearing parents of deaf children have regardless of the communication options and aids they select, such as sign language, hearing aids, cued speech or cochlear implants (Eleweke, Gilbert, Bays, & Austin, 2008;Jackson, Traub, & Turnbull, 2008;Jackson, Wegner, & Turnbull, 2010;Meadow, 1980). Whereas there is evidence that parents of deaf children need support, there remain questions about parents' needs for support given that many of them have successively, and in a short period of time experienced: the diagnosis of deafness, the decision-making and candidacy process for a CI, and their child's surgery.…”
Section: Parental Needs For Postoperative CI Services and Supportmentioning
confidence: 99%
“…(Meadow-Orlans et al, 2003;Nicholas & Geers, 2006). Researchers consistently emphasize the importance of professionals' roles in guiding, supporting, and informing parents regarding the progress of deaf children, including not only hearing, but functioning in their daily environments as well (DesJardin et al, 2006;Eleweke et al, 2008;Incesulu et al, 2003;Zaidman-Zait & Most, 2005).…”
Section: Everyday Challenges and Cismentioning
confidence: 99%